Chronic Obstructive Pulmonary Disease Guidelines in Europe: a Look Into the Future - Miravitlles, M (2018)
Clinical practice guidelines are ubiquitous and are developed to provide recommendations for the management of many diseases, including chronic obstructive pulmonary disease. The development of these guidelines is burdensome, demanding a significant investment of time and money. In Europe, the majority of countries develop their own national guidelines, despite the potential for overlap or duplication of effort. A concerted effort and consolidation of resources between countries may alleviate the resource-intensity of maintaining individual national guidelines. Despite significant resource investment into the development and maintenance of clinical practice guidelines, their implementation is suboptimal. Effective strategies of guideline dissemination must be given more consideration, to ensure adequate implementation and improved patient care management in the future.